Thiol- and Disulfide-Based Stimulus-Responsive Soft Materials and Self-Assembling Systems - Danielle M. Beaupre (Molecules, 2021)
Properties and applications of synthetic thiol- and disulfide-based materials, principally polymers, are reviewed. Emphasis is placed on soft and self-assembling materials in which interconversion of the thiol and disulfide groups initiates stimulus-responses and/or self-healing for biomedical and non-biomedical applications.